The Effect of Single Edge Notch Bend (SENB) Specimen Geometry to Fracture Properties of Aluminium Alloys Using Simulation Analysis - Alias, Anas; Abdul Latif, Noradilla (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Aluminium alloys are strong yet light metals that are found uses in almost every market. An alloy is the mixture of metals which will be more useful when mixed than their constituent metals alone. Aluminium alloys are widely used as structural materials in aeronautical industries due to their attractive comprehensive properties such as low density, high strength, ductility, toughness and resistance to fatigue. Single Edge Notch Bend (SENB) specimen is an American Society for Testing and Materials E1820 standard fracture toughness testing specimen geometry. SENB specimen is a rectangular beam with a single edge notch under three point bend load. In this study is about the effect of single edge notch bend (SENB) specimen geometry to fracture properties of Aluminium alloys using simulation analysis. The finite element analysis, ANSYS software has been used to simulate the three point bending and four point bending test. The mechanical properties of the Aluminium alloys from the simulation analysis is studied and compared to the result from the previous research. The findings shows that narrow notch specimen has the highest equivalent stress which is 1316.1 MPa, 1974.2 MPa and 2632.3 MPa for the respective load and the equivalent strain is 0.018649, 0.027974 and 0.037298 for the three point bending simulation test. For four point bending, four point bend specimen shows the highest equivalent stress at 869.29 MPa, 1303.9 MPa and 1738.6 MPa for the respective load. Equivalent strain is 0.0095638, 0.014 346 and 0.019128 for the AL6061-T6 material. This shows that the equivalent stress is increase when the load is increase. The material AL6061-T6 has the highest stress because of the chemical composition in the material. All material shows the plastic behavior on the specimen and at notch tip. This is because the higher the amount of plastic strain and the bigger plastic zone indicate the higher resistance towards notch opening on the specimen when the load increase.